# What is going wrong in this “proof” of $0=1$? [closed]

\begin{align} -20 &= -20\\ 16-36 &= 25-45\\ 4^2-4\times 9&=5^2-5\times 9\\ 4^2-4\times 9+81/4&=5^2-5\times 9+81/4\\ 4^2-4\times 9+(9/2)^2&=5^2-5\times 9+(9/2)^2\\ \end{align}

Considering the formula $$a^2+2ab+b^2=(a-b)^2$$, one has \begin{align} (4-9/2)^2&=(5-9/2)^2\\ \sqrt{(4-9/2)^2}&=\sqrt{(5-9/2)^2}\\ 4-9/2&=5-9/2\\ 4&=5\\ 4-4&=5-4\\ 0&=1 \end{align}

## closed as off-topic by Elliot G, BruceET, Claude Leibovici, user91500, Ian MillerDec 31 '16 at 11:10

This question appears to be off-topic. The users who voted to close gave this specific reason:

• "This question is missing context or other details: Please improve the question by providing additional context, which ideally includes your thoughts on the problem and any attempts you have made to solve it. This information helps others identify where you have difficulties and helps them write answers appropriate to your experience level." – BruceET, Claude Leibovici, user91500, Ian Miller
If this question can be reworded to fit the rules in the help center, please edit the question.

• $\sqrt{x^2}=|x|$ so $\sqrt{a^2}=\sqrt{b^2}$ does not imply $a=b$ but rather $|a|=|b|$. And, indeed, $|4-9/2|=|5-9/2|=1/2$ but $4-9/2 \ne 5-9/2$ and the rest doesn't follow. – dxiv Dec 31 '16 at 3:44
• I don't see why this question keeps getting downvotes. I'll give it a +1 just because it is very clearly titled "spot the mistake", it is written down in full detail, and correctly tagged as fake-proofs. – dxiv Dec 31 '16 at 4:12
• Possible duplicate of Best Fake Proofs? (A M.SE April Fools Day collection) – Moo Dec 31 '16 at 4:16

Here let me simplify your process:

\begin{align} (-2)^2 = 4 &\implies \sqrt{(-2)^2} = \sqrt{2^2} \\ &\implies -2 = 2 \\ &\implies -2 + 2 = 2 +2 \\ &\implies 0 = 4 \end{align}

QED. Do you see the mistake?

$\sqrt {a^2}\ne a$. You should never have been taught that it does.

Instead $\sqrt {a^2}=|a|$ .

So....

$(4-9/2)^2=(5-9/2)^2$

$\sqrt {(4-9/2)^2}=\sqrt {(5-9/2)^2}$

$|4-9/2|=|5-9/2|$

$4 - 9/2 = \pm 5 \mp 9/2$

$4 = 5$ or $4 = -5 +2* 9/2=-5+9$

$4-4=5-4$ or $4-4 =-5-4+9$

$0=1$ or $0 = 0$

• So, I'm simply give the answer: we cannot root the negative integer,as in question &radic;(4-9/2)<sup>2</sup>=&radic;(5-9/2)<sup>2</sup> explaination: LHS:4-9/2=(8-9)/2 so &radic;((8-9)/2)<sup>2</sup> &radic;(-1/2)<sup>2</sup> &radic;(1/4) (1/2) RHS:5-9/2=(10-9)/2 so &radic;((10-9)/2)<sup>2</sup> &radic;(1/2)<sup>2</sup> &radic;(1/4) (1/2) LHS=RHS – Animesh Sahu Dec 31 '16 at 17:00
• Not quite. $(5-9/2)^2 = 1/4$ and $(4-9/2)^2 = 1/4$ and that's fine. But if $a^2 = b^2$ that does NOT mean $a = b$. The problem $x^2 = 25$ has two answers. $x = 5$ is one answer but $x = -5$ is another. If $c > 0$ then there is one positive number $r$ so that $r^2 = c$ and there is one negative number that is equal to $-r$ so that $(-r)^2 = c$. So $a^2 = b^2$ does not mean $a = b$ but it means $|a| = |b|$ but either a or b could be positive or negative. So you have $(4-9/2)^2 = (5-9/2)^2$ which is fine But 4 - 9/2 < 0 while 5 - 9/2 > 0. so... to be continued... – fleablood Dec 31 '16 at 17:36
• ... continued.... and you have $(4-9/2)^2 = (5-9/2)^2$ which is fine (they both equal $1/4$). And you have $\sqrt{(4- 9/2)^2} = \sqrt{5-9/2)^2}$ which is also fine (they both equal $1/2$). But you have $\sqrt{(4-9/2)^2} = 4-9/2 = - 1/2$ which is NOT fine. This isn't true. $\sqrt{(-5)^2} = \sqrt{25} = 5 \ne -5$. $\sqrt{a^2} \ne a$--- you should never have learned that. $\sqrt{a^2} = |a|$. $|a| = 0$ if $a \ge 0$ but $|a| = -a$ if $a \le 0$. So you can conclude $|4- 9/2| = |5-9/2|$ which is fine. They both equal 1/2. – fleablood Dec 31 '16 at 17:43